Inflammatory breast carcinoma - Ha, Kelli Y. (Baylor Health Care System, 2013)
Inflammatory breast carcinoma is a rare form of invasive breast cancer often characterized by erythema, warmth, and a classic “peau de orange” or “orange peel” appearance of the affected breast. The average age of onset is within the fourth and fifth decades. Lesions are usually detected and evaluated with mammography, sonography, and recently, breast magnetic resonance imaging. We present the case of a 49-year-old woman with inflammatory breast carcinoma in her left breast and describe the imaging appearance of this aggressive lesion on the modalities listed above. Because this lesion may be misdiagnosed as infection (i.e., mastitis) or as the sequelae of a dermatologic disorder, proper characterization of inflammatory breast carcinoma is of the utmost clinical and radiologic importance.